2007
DOI: 10.1016/j.plasmid.2006.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of the gonococcal 5.2kb β-lactamase plasmid pSJ5.2 into Escherichia coli by cointegration with several gram-conjugative plasmids

Abstract: We report the mobilization by cointegration of the gonococcal 5.2 kb beta-lactamase plasmid pSJ5.2 in an Escherichia coli background. Transfer of pSJ5.2 was measured by filter mating assays with five different conjugative plasmids from Enterobacteriaceae and the gonococcal 41 kb tet(M). Plasmid pSJ5.2 was mobilized to E. coli at frequencies of 1.7x10(-6), 9.3x10(-8) and 2.7x10(-5) by the tet(M), R64 drd-33 and N3 conjugative plasmids, respectively. Mobilization of pSJ5.2 by the 41 kb tet(M) conjugative plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Sequences from the beta-lactamase plasmid conferring resistance to beta-lactams were retrieved from plasmid pSJ5.2 containing bla TEM1 , and defined as NEIS2357–NEIS2360 (DQ355980) with NEIS2357 designating the bla TEM gene (Table 1). 21 …”
Section: Methodsmentioning
confidence: 99%
“…Sequences from the beta-lactamase plasmid conferring resistance to beta-lactams were retrieved from plasmid pSJ5.2 containing bla TEM1 , and defined as NEIS2357–NEIS2360 (DQ355980) with NEIS2357 designating the bla TEM gene (Table 1). 21 …”
Section: Methodsmentioning
confidence: 99%
“…Previously published physical maps of the N3::pSJ5.2 and R64::pSJ5.2 cointegrate DNA of transconjugants with BamH1 and HindIII revealed that a region within the 1.8 kb BamH1-HindIII fragment of pSJ5.2 is deleted during fusion with the R64 and N3 plasmids (Scharbaai-Vázquez et al ., 2007; Region B in Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The 5.2 kb beta-lactamase plasmid from Neisseria gonorrhoeae (the gonococcus) is one of the three small broad-host range and mobilizable resistant (R)-plasmids associated with the worldwide spread and prevalence of Pennicillinase-Producing Neisseria gonorrhoeae (PPNG) infections (Phillips, 1976; Ray et al, 2005; Scharbaai-Vázquez et al, 2007). The 5.2 kb R-plasmid is a mob/oriT deletion derivative of the parental 7.4 kb R-plasmid (Dillon et al, 1991; Pagotto et al ., 2000; Candelas, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations